Various risks and safety analysis to reduce fire in oil refinery plant. Issue 1 (February 2021) - Alam, Md Zahangir; Sakib, Md Nazmus; Islam, Minarul; Jalal Uddin, Mohammad
Abstract: It is quite hazardous to produce the final product of oil or gas in a petrochemical refinery plant due to its flammable or combustible and explosive materials. Small mistakes can cause massive damage to life, property, pollution, injury, ecosystem, and business by fire. The entire system is challenging to manage. Therefore, fire risk assessment and forecasting are necessary to overcome personal, environmental, and refinery plants' hazard situations. There have been four main threats in any refinery facility: electrical, mechanical, civil, and chemical issues, maximum cases its result burning. This research aimed to study and assess fire risk in the refinery plant by using a multi-stage early warning system and reducing the fire. The fire hazard safety layer technique would be used for our petrochemical process. Some equipment is set in place to forecast the danger and execution before and after it happens. Geographic information systems (GIS), remote sensing (RS) are some techniques for fire incidents tracking. Flame detectors, heat detectors, and gas detectors are used to maintain good contact in the entire risk analyzer portion. Various techniques and monitoring have been proposed to operate the plant efficiently and safely, like controlling, predicting, and pre-warning strategic planning.